Self-esteem as a mediator variable between cyber bullying and depression - Paguntalan, Gerluellen B. (2014.)
Cyber bullying is a worldwide phenomenon that is happening today. It is a collective label of bullying that uses electronic means like the internet or mobile phones to intentionally harm someone (Price and Dalgleish, 2010). Low self-esteem and depression are two of its most common effects. The purpose of this study was to establish the relationship between cyber bullying, self-esteem, and depression. One hundred and fifty high school students from Jaro National High School in Iloilo City were asked to answer a three-part questionnaire assessing their experiences with cyber bullying, relational-verbal bullying, physical bullying, and bullying based on culture. It was followed by the assessment of their self-esteem, and their depression state. Results dictated that there was no significant correlation between self-esteem, cyber bullying, and depression. Although, cyber bullying, relational-verbal bullying, and physical bullying, had a positive correlation with depression, self-esteem did not yield a significant correlation with depression and any of the four types of bullying. This meant that self-esteem cannot be established as a mediating variable between cyber bullying and depression. Cyber bullying did not affect an individual?s self-esteem. An individual?s self-esteem did not also affect his state of depression.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2014.
Keywords: Cyber Bullying -- Research; Depression -- Research